Hubungan Kegiatan Bermain Kooperatif terhadap Empati Anak di PAUD Asmaul Husna - Jaliha Kadir; Tiara Meilia Lamatiti; Qur Ana M Yadasang (Institut Nalanda, 2025)
This study aims to analyze the relationship between cooperative play activities and the development of children's empathy in Early Childhood Education. Cooperative play is an activity that emphasizes interaction, cooperation, sharing, and support between peers. This activity is believed to be able to encourage children to understand and respond to the feelings of others better. The study used a quantitative approach with a correlational method, involving participants aged 4–6 years at PAUD Husna. Data were collected through structured observation and empathy assessment scales that were adjusted to early childhood characteristics. The analysis of the results showed a significant positive correlation between the intensity of cooperative play activities and the level of empathy of children. These findings confirm that children's involvement in cooperative play not only serves as a means of entertainment, but also as an effective social and emotional learning medium. This study provides practical implications for educators and parents to better integrate cooperative play activities into the curriculum and daily activities. Thus, the development of children's empathy can be done naturally through fun play experiences, while supporting the formation of better social skills in the future.